Development of E-Worksheet Based on Technological Pedagogical Content Integrated Discovery Learning to Improve Students' Critical Thinking Skills in Colloidal Materials - Sari, Devi Novita; Winarti, Atiek; Saadi, Parham; Abrori, Fadlan Muchlas; Iriani, Rilia (Universitas Syiah Kuala, 2025)
The main problem in this study is the low level of students critical thinking skills (CTS) in chemistry learning caused by ineffective learning models that do not support CTS development. The importance of CTS has not been reflected in classroom practices. Therefore, this study aims to determine the validity, practicality, and effectiveness of a TPACK-integrated discovery learning-based E-worksheet in improving students CTS on colloidal materials. This research uses the research and development (RD) method with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The research subject CTS consisted of five validators and 33 students of class XII Science 1 at SMAN 1 Alalak. Data were collected using test and non-test instruments, and analyzed descriptively to determine the levels of validity, practicality, and effectiveness of the developed e-worksheet. The results show that: (1) the e-worksheet is highly valid based on content, presentation, language, and media aspect CTS; (2) it is very practical based on readability tests, student and teacher responses, and teacher ability and learning implementation observations; and (3) it is effective, as evidenced by the significant improvement of students CTS categorized as high. In conclusion, the TPACK-integrated discovery learning-based e-worksheet is valid, practical, and effective as a teaching material in chemistry learning on colloidal materials to enhance students CTS